Evidence of intrauterine device insertion by nurses in Primary Health Care: an integrative review - Lays Souza de Oliveira; Patrícia Madalena Vieira Hermida; Elizimara Ferreira Siqueira; Juliana Cipriano Braga Silva de Arma; Larissa Scheeren Thomas; Indiara Sartori Dalmolin (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to synthesize and analyze evidence on intrauterine device insertion by nurses in Primary Health Care. Methods: an integrative review, carried out in the BDENF, CINAHL, LILACS, SciELO, Scopus, PubMed and Web of Science databases in June 2022, delimiting the period from 1960 to 2022. Results: 141 articles were identified in the initial search, and 10 studies made up the final sample. Four (40%) were developed in the United States and one (10%) in Brazil, with publications from 1979 to 2021. The findings were grouped into three categories: Nurse training to insert an intrauterine device; Nurses' competency to insert an intrauterine device; and Women's access to intrauterine devices. Conclusions: nurse theoretical and practical training is a prominent element, consolidated in the favorable outcomes of insertions performed by nurses and satisfaction among women, a practice that has expanded access to the contraceptive method in Primary Health Care.